Development and performance evaluation of grape debunching machine for production of raisins and stemless table grapes. (6th October 2021) - Pawar, Dilip A.; Giri, Saroj K.; Sharma, Ajay K.
Abstract: Chemical pretreatment before drying is a practice in raisin making which has many limitations and use of chemical shall be discouraged. A new process is being developed with physical pretreatment. The process requires intact grape berries for further processing. Therefore, a grape debunching machine has been developed for separation of intact berries from the bunch. The machine consists of central rotor with helical fingers. The rotor assembly is surrounded by perforated trough through which the detached berries drop. The performance of the machine was evaluated with "Thompson Seedless" table grape for debunching efficiency and damage to berries. The rotor speed (80–120 rpm) and concave clearance (5–25 mm) were selected as independent parameters. The debunching efficiency and percentage of damaged berry were in the range of 77.17–98.73% and 5.75–11.82%, respectively. The maximum debunching efficiency (94.33%) and minimum berry damage (7.10%) was obtained at rotor speed of 100 rpm and concave clearance of 15 mm. The capacity of grape debunching machine was found to be 145.2–150.2 kg/hr for different grape varieties, namely Thompson Seedless, Manik Chaman, and Fantasy Seedless. The developed machine will be useful in production of raisins without use of chemicals and stemless table grapes. Practical applications: The conventional process of raisin making involves intensive use of chemicals right from dipping of harvested grape bunch in a solution of ethyl oleate (1.5%) and potassium carbonate (2.5%), intermittent sprays, and further use of booster and sulfur dioxide for color improvement. The intensive use of chemicals triggers the food safety issues. Furthermore, the process requires longer drying time, involves more number of unit operations, and fetches losses of grapes. To address these issues, an alternative chemical‐free process has been developed by the authors of this investigation for the production of raisins. This process requires the grape berries to be individualized before further processing which is tedious and time consuming if done manually. Therefore a grape de‐bunching machine has been developed for separation of intact grape berries which can be further processed into raisins at industrial scale without use of chemicals. The developed machines will find applications in the minimally processed/individual quick freezing (IQF) of table grapes for which there is an increasing market especially in super market.